Synthesis of the pentasaccharide repeating unit of the O-antigen of E. coli O117:K98:H4 - Mandal, Pintu Kumar (Beilstein Journal of Organic Chemistry, 2014)
The pentasaccharide repeating unit of the O-antigen of E. coli O117:K98:H4 strain has been synthesized using a combination of sequential glycosylations and [3 + 2] block synthetic strategy from the suitably protected monosaccharide intermediates. Thioglycosides and glycosyl trichloroacetimidate derivatives have been used as glycosyl donors in the glycosylations.
Keywords: Escherichia coli; glycosylation; lipopolysaccharide; O-antigen; pentasaccharide